Perception of stakeholders on current perfusion education in Malaysia / Rafiq Sumardi Omar - Rafiq Sumardi, Omar (2021)
Perfusionist is known as a certified medical technician liable for extracorporeal oxygenation of the blood during open-heart surgery. Current curriculum is believed to be at par and is aligned with the National Occupational Skills Standard, however, the scope of perfusion practice keeps changing with the advancement of technology and procedures, and there is a demand for specialty area such as extracorporeal membrane oxygenation (ECMO). Therefore, current curriculum should be re-evaluated by taking consideration from multiple stakeholders’ perception on current needs, content, educational strategies, teaching methods, assessment methods, and curriculum management. Hence, this study aimed to explore perception of stakeholders in evaluating current perfusion education in Malaysia. In the context of the present study, stakeholders of perfusion education in Malaysia were referred to the private providers, manager, educators, advance diploma holders, perfusionist, and pensioners. This was a qualitative study which involved in-depth interview approach. A total 10 stakeholders participated in this study, chosen though purposive sampling. The interview was guided by semistructured questions to explore participant’s perception. The participants were approached by the list obtained from the Malaysian Perfusionist Society (MAPS). The interviews were conducted face-to-face or virtually. Interviews were conducted in English and Malay languages. The Malay conversation was transcribed into English. The ethical approval was obtained from University’s research ethic committee. The interview transcripts were analyzed using thematic analysis to address the four components of Daniel Stufflebeams’s conceptual model for programme evaluation: Context, Input, Process, and Product. Based on the findings, in terms of the context code, perfusion programme can be improved by competency acquisition, proper accreditation, having longer duration of study, benchmark the curriculum, and integrate simulation-based 4 training. In terms of input evaluation, the strengths of the institutions were having sufficient cardiac cases and certificate recognition. However, few weaknesses were identified, namely the programme is not par with international standard, lack of clinical experience among trainees due to time constraint, and non-comprehensive syllabus. For the process evaluation, modifications to improve perfusion educations include to upgrade existing diploma to degree level, encourage critical thinking through evidence-based practice, reduce knowledge and practice gap, and to have single exit exam which serve as standard assessment. As for the product evaluation, current perfusionist trainees were less competent and the scope of perfusion need to be widened to cater for the advancement in the field of perfusion. In conclusion, it is hoped that further steps can be taken to improve the quality of perfusion education in Malaysia, including the absorption of competency-based education where the number of cases collected should be the priority to qualifying individual perfusionist. This can be done through three mechanisms such as the training centres should have adequate number of clinical cases to provide learning opportunities for the students, prolonging the duration of study, and providing interdepartmental or inter hospital rotation clinical placements. Keywords: Perception, stakeholders, perfusion education, Malaysia